2018
DOI: 10.12955/cbup.v6.1236
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology and Seniors

Abstract: Goal: This article focuses onthe relationship between information technologies and theiruse by senior citizens. The main objective of the research is to identify the problems that encompasssenior citizenuse of information technologies.Methods: The research sample consisted of 5 participants aged 62 years to 66 years, from which 2 participants were women and 3 were men. The research method used was a semi-structured interviews of own design.Results: The largestbarrier between information technology and senior c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…We did not include studies already reported in the systematic reviews as individual studies to avoid duplication. Clinical trial intervention studies (RCTs and non-RCTs) were conducted in Finland, France, the Netherlands [ 35 , 39 ], Taiwan [ 38 ], the United States [ 36 , 40 - 42 , 44 , 64 ], Australia [ 34 , 37 ], New Zealand [ 43 ], Germany [ 61 ], Slovakia [ 62 ], Italy [ 59 ], and Sweden [ 45 ]. Except for Iran [ 60 , 63 ], no studies were conducted in low- to middle-income countries (LMICs).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not include studies already reported in the systematic reviews as individual studies to avoid duplication. Clinical trial intervention studies (RCTs and non-RCTs) were conducted in Finland, France, the Netherlands [ 35 , 39 ], Taiwan [ 38 ], the United States [ 36 , 40 - 42 , 44 , 64 ], Australia [ 34 , 37 ], New Zealand [ 43 ], Germany [ 61 ], Slovakia [ 62 ], Italy [ 59 ], and Sweden [ 45 ]. Except for Iran [ 60 , 63 ], no studies were conducted in low- to middle-income countries (LMICs).…”
Section: Resultsmentioning
confidence: 99%
“…Original articles were either qualitative [ 36 - 38 ] or used mixed methods [ 39 , 40 ]. Various methods were used to measure the outcome of interest, including cognitive walk-throughs [ 44 ], semistructured interviews [ 37 , 39 , 42 - 44 , 61 , 62 , 64 ], in-depth interviews [ 40 ], focus groups [ 45 , 59 ], and web-based surveys [ 39 - 41 ]. The Technology Acceptance Model [ 38 ] and the Unified Theory of Acceptance and Use of Technology Model [ 48 ] were also used to assess the feasibility of ICT interventions in 2 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These potential users that may be willing to adopt mobile devices and banking need to understand how to use the new technology (Choudrie et al, 2018). Pikna et al (2018) found that a substantial hindering factor faced by the elderly is the modernisation of technology, which puts pressure on their competencies. Komninos et al (2014) maintain that the design of technology for the elderly's needs should consider the psychological, physiological, cognitive and societal factors.…”
Section: Mobile Banking and The Elderlymentioning
confidence: 99%
“…The elderly represent a significant business opportunity for online marketers [9], and it may be a missed opportunity if the elderly's needs are not catered for in the technology rollout. Technology continuously changes and the elderly lack educational opportunities to keep up with it [10]. Some authors indicate that it is not always clear whether the elderly will participate actively on the online and mobile commerce solutions [7].…”
Section: Introductionmentioning
confidence: 99%